2013
DOI: 10.1021/jp3103035
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Monomeric Chromium(VI) Oxide Species Supported on Silica: Periodic and Cluster DFT Studies

Abstract: International audienceSilica-supported chromium oxide systems are efficient catalysts for many important chemical processes. Despite many years of investigations, the structure of the surface Cr species is not unambiguously determined. In this work, comprehensive DFT investigations of the monomeric Cr(VI) oxide species on silica under dehydrated conditions are performed. A large number of advanced periodic and cluster models of the SiO2 surface, based on the beta-cristobalite structure and different amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
119
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(137 citation statements)
references
References 73 publications
18
119
0
Order By: Relevance
“…Deconvolution of the H 2 -TPR spectrum of the supported 3 % CrO x /SiO 2 catalyst found that the surface chromia phase consists of *2/3 surface dioxo sites and *1/3 surface mono-oxo sites (exact dioxo:mono-oxo ratio *1.7). These findings are in agreement with the DFT calculations by Handzlik et al that predicted that dioxo surface (O=) 2 CrO 2 sites should be much more stable than monooxo surface O=CrO 4 sites on the SiO 2 support [19]. The H 2 reduction kinetics for the surface dioxo and mono-oxo chromia sites on silica are also provided from the peak temperatures (Tp) during the H 2 -TPR experiments by application of the Redhead equation for first-order reactions [34,35].…”
Section: Activation Of Well-defined Catalystssupporting
confidence: 93%
See 1 more Smart Citation
“…Deconvolution of the H 2 -TPR spectrum of the supported 3 % CrO x /SiO 2 catalyst found that the surface chromia phase consists of *2/3 surface dioxo sites and *1/3 surface mono-oxo sites (exact dioxo:mono-oxo ratio *1.7). These findings are in agreement with the DFT calculations by Handzlik et al that predicted that dioxo surface (O=) 2 CrO 2 sites should be much more stable than monooxo surface O=CrO 4 sites on the SiO 2 support [19]. The H 2 reduction kinetics for the surface dioxo and mono-oxo chromia sites on silica are also provided from the peak temperatures (Tp) during the H 2 -TPR experiments by application of the Redhead equation for first-order reactions [34,35].…”
Section: Activation Of Well-defined Catalystssupporting
confidence: 93%
“…The corresponding Raman spectrum, with 442 nm laser excitation, exhibited bands at 987 (s) and 1014 (m) cm -1 , and the selective reduction of the 987 cm -1 band by H 2 showed that both bands originate from two distinct surface CrO x sites on silica [14]. Corresponding isotopic 18 [19]. This suggests that the surface dioxo CrO 4 species should have a higher concentration than the surface mono-oxo CrO 5 species on the silica support (as will be experimentally shown below with H 2 -TPSR).…”
Section: Hydrated Supported Cro X /Sio 2 In Initial Oxidizedmentioning
confidence: 99%
“…It is believed that anatase titania in the equilibrium morphology displays primarily the (101) surface [71]. Amorphous silica has often been modeled as a surface of crystalline β-cristobalite [72,73]. Here we used (001) surface of β-cristobalite, which has shown to resemble amorphous silica very closely [73].…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Amorphous silica has often been modeled as a surface of crystalline β-cristobalite [72,73]. Here we used (001) surface of β-cristobalite, which has shown to resemble amorphous silica very closely [73]. The surfaces were considered to be dehydrated corresponding to the high calcination temperature of the samples.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…1). For the comparisons made here, it will be assumed [78] that the dispersion of the Ni 2? species at the defect sites of MCM-41 is controlled by their thermodynamic stability and not by any kinetic phenomenon in the preparation method.…”
Section: Resultsmentioning
confidence: 99%